The Importance of Understanding Internal Accounting in Everyday life - Ayu, Adriyani Puspita; Azim, Muhammad; Damayanti, Sri (Business Management, 2024)
Accounting is not just about calculating numbers and translating data into financial reports. More than that, Accounting is a science that equips individuals with the ability to manage finances,analyze data,and make wise decisions. Whether someone aims to manage personal finances more efficiently, run a business with more structure, or even understand the impact of financial decisions on a large scale. Therefore, in this research, we will discuss in more depth the importance of knowing accounting in everyday life. The aspects that will be discussed are the application of accounting in everyday life, the benefits of accounting in life, and what accounting activities are in everyday life.